KELAYAKAN BOOKLET JAMUR KELAS X SMA DARI HASIL INVENTARISASI JAMUR MAKROSKOPIS - Romika Romika; Laili Fitri Yeni; Andi Besse Tenriawaru (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aimed to determine the feasibility of the booklet from the inventory of macroscopic fungi in the Pikul Customary Forest of Bengkayang Regency as a teaching medium on mushroom material.The research method used is descriptive with quantitative research form.The booklet in this study resembles a book in that there is an introduction, content and closure.Booklet validation was carried out by 5 validators consisting of 2 lecturers of Biology Education, Faculty of Teacher Training and Education, Tanjugpura University and 3 Biology teachers in class X SMA.The results of booklet validation were analyzed using Lawshe by calculating the Content Validity Ratio (CVR) and the Content Validity Index (CVI).The CVR and CVI results from 5 validators obtained a value of 0.99 so that the booklet was declared valid as a learning medium on the material of mushroom class X SMA.